Pengaruh Ukuran Perusahaan, Pertumbuhan Aset Dan Pertumbuhan Penjualan Terhadap Stuktur Modal Pada Perusahaan Sektor Kesehatan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Musyayada, Afina Zahida; Rukmini; Ningsih, Suhesti (Nur Science Institute, 2025)
This study aims to analyze the effect of firm size, asset growth, and sales growth on capital structure in healthcare companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. The research population consisted of 30 companies, from which 20 firms were selected as samples using purposive sampling. Data were obtained from annual financial reports and analyzed using multiple linear regression with classical assumption tests, t-test, F-test, and the coefficient of determination. The results show that firm size and sales growth have a significant positive effect on capital structure, while asset growth has no significant effect. These findings support the trade-off theory, which explains that larger firms have easier access to external financing, and the pecking order theory, which suggests that sales growth increases the need for external funding. The implication of this study is that healthcare companies should consider firm size and sales performance when making capital structure decisions.